Síntese e caracterização de emulsões óleo em água para injeção em meios porosos - Assunção, Leticia Silveira Dias de (2022)
The injection of oil-water emulsions (O/W) is an oil recovery method, which remained in control of the mobility of the injected fluid, has the potential to increase the volume of oil recovered. For the mechanism to work properly, in addition to knowing the characteristics of the reservoir, it is extremely important to understand the physical properties of the emulsion. For this purpose, in this research eight synthetic emulsions were prepared, composed of 10% of oil phase (paraffinic mineral oil ALOGRO M600) and 90% of aqueous phase. The influence the by the variation in the concentration (0,20%, 0,30%, 0,40% e 0,50%) of the mixture of the mixture of two non-ionic surfactants (Span 80® and Tween 80®). The prepared experiments were characteristic through their kinetic stability, appearance and droplet size experience (DTG). The emulsion selected for injection into the porous medium was synthesized with 0.40% concentration of the surfactant mixture, emulsified at a rotation of 10,000 rpm for 5 min. The results proved that this emulsion was kinetically stable and presented an average value of droplet size in the range of 2 µm. The emulsion showed a pseudoplastic behavior, with an average apparent frequency of 98.47 mPas. The effect of emulsion injection in a porous medium was thought through the behavior of the injection pressure for the rotation of water injection and emulsion injection. Three experiments were carried out on two samples of sandstone and one carbonate rock, with different permeabilities. The results of the recovery experiments show that the water injection results in a recovery factor of 41.56% and the emulsion injection led to an increase in the injection pressure of 0.323 kgf/cm² in the rock sample with the highest permeability